Temperature dependent relocation of the cesium primary ion beam during SIMS analysis. (7th August 2014) - Giordani, Andrew; Tuggle, Jay; Winkler, Christopher; Hunter, Jerry; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> The ability to control and accurately measure the cesium concentration, [Cs], is a critical step toward understanding the role of Cs in the SIMS MCs+ technique. We have developed a method to alter the instantaneous [Cs] by using electron gun heating (in situ) during Cs bombardment and found that heating (ex situ) during the X‐ray photoelectron spectroscopy (XPS) analysis provides a qualitative depth distribution of the implanted Cs. The effectiveness of in situ and ex situ heating is explored on (100) silicon and (100) indium arsenide. Cs build‐up curves are studied to determine if in situ heating produces secondary ion yields that are favorable for the MCs+ technique. In addition to XPS, scanning electron microscopy/energy dispersive spectroscopy (SEM/EDS) and scanning transmission electron microscopy/energy dispersive spectroscopy (STEM/EDS) are utilized to measure [Cs]. The goal of this work is to improve the quantification of the MCs+ technique used in SIMS by understanding the material dependent behavior (incorporation and retention) of Cs and how it affects the MCs+ analysis. Copyright © 2014 John Wiley & Sons, Ltd.